Extraction of cannabinoids by hexane from polar organic solvents and their mixtures with water - Mikhniuk, Olga N.; Leschev, Sergey M.; Zayats, Mikhail F.; Kypchenya, Dmitry S.; Nikandrava, Yana L.; Yurchenko, Ruslan A. (Journal of the Belarusian State University. Chemistry, 2024)
Distribution constants of cannabidiol, cannabinol and tetrahydrocannabinol in systems hexane – polar organic solvents (methanol, ethanol, propylene glycol, ethylene glycol, diethylene glycol, 2-methoxyethanol, dimethyl sulfoxide, dimethylformamide, acetonitrile) and hexane – aqueous organic mixtures were determined experimentally. Gas chromatography with mass spectrometric detection was used to determine the concentrations of substances in solutions. Based on the obtained data, a sample preparation technique for determining cannabinoids in objects of plant origin was proposed.